Breastfeeding Patterns in Stunted and Not Stunted Toddlers Using Infant Feeding Area Graphs in the Working Area of the Pagambiran Health Center, Padang - Sari, Maharani Permata; Yusrawati; Afdal; Desmawati; Arni Amir; Finny Fitry Yani (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the nutritional problems of children in Indonesia is stunting. Fulfillment of nutrition in the first 1,000 days of life is related to stunting. WHO recommends breastfeeding and breastfeeding as a method of feeding babies to achieve optimal growth and development. This descriptive study aims to provide an overview of the feeding practices of stunted and non-stunting toddlers as seen in the feeding history included in the Toddler Feeding Area Chart from 0-6 months of age. This research found that giving breast milk alone to stunted toddlers (52.17%) was lower than non-stunting toddlers (66.67%), and the most common feeding pattern for stunted toddlers was formula milk.